Domestic Activities Associated With a Decreased Risk of Cognitive Disorders: Results of the “Fréle” Cohort - Dupré, Caroline; Hupin, David; Goethals, Luc; Béland, François; Roche, Frédéric; Célarier, Thomas; Carrière, Isabelle; Barth, Nathalie; Bongue, Bienvenu (Frontiers in Public Health, 2020)
Background: Previous cohorts studied the association of various types of physical activities with the incidence of cognitive disorders. The objective of this work was to analyze the association of leisure, domestic and professional physical activities with mild and moderate cognitive disorders in older people living in the community. Methods: We used retrospective data from the “FRéLE” (FRagilité: étude Longitudinale de ses Expressions) a longitudinal and observational study. Data collected included socio-demographic variables, lifestyle and health status. Cognitive disorders were assessed using the Montreal Cognitive Assessment (MoCA). Two cut-offs of MoCA were used to analyze mild and moderate cognitive disorders. Physical activity was assessed by the Physical Activity Scale for the Elderly (PASE) structured in three sections: leisure, household, and professional activities. Spline and logistic regression models were used to estimate the risk of cognitive disorders. Results: At baseline, 428 participants (for study of mild disorders) and 1,271 participants (for study of moderate disorders) without cognitive disorders were included in the analysis. The mean ages were 74 and 78 years, respectively. After a 2-year follow-up, we found mild cognitive disorders in 154 participants (36%) and 71 cases of moderate cognitive disorders (5.6%). In multi-adjusted logistic models, domestic activities were associated with cognitive disorders, but not leisure and professional activities. Conclusion: We found an inverse relation between domestic sub-score and cognitive disorders defined by MoCA < 18. With a specific questionnaire and quantitative information on the type of activities, this study contributed to the debate on the beneficial effects of physical activity on cognition.